The feasibility of endoscopic autogenous fat transplantation in the treatment of gastroesophageal reflux disease: An animal pilot study - Xin Huang; Xiaoying Wang; Changqing Zhong (Gastroenterology & Endoscopy, 2024)
Objective: Endoscopic injection is one of the simplest minimally invasive methods for the treatment of gastroesophageal diseases. However, the safety of injection material limits its clinical application. We investigated the feasibility, safety and efficacy of endoscopic autogenous fat transplantation (EAFT) in the lower part of esophagus in the treatment of gastroesophageal reflux disease in New Zealand albino rabbits. Methods: Eight New Zealand albino rabbits were used for autogenous fat transplantation. The dynamic pH value of the lower esophagus was monitored before and one week after fat transplantation in two rabbits. The local retention of fat was observed by endoscopy, and the pathological analysis was made at the junction of esophagus and stomach after two weeks of fat transplantation in six albino rabbits. During the experiment, the weight, dietary habit and infection of albino rabbits were monitored. Results: Endoscopic autogenous fat transplantation of the lower esophagus was successfully performed in 8 albino rabbits. The average pH value of the esophagus increased from 5.6 to 7.5 and 7.4 to 7.9, respectively in two rabbits one week after transplantation. The fat barrier of the lower esophagus was remained locally and observed by endoscopy two weeks after transplantation in six rabbits. Pathology showed that the adipocytes survived in the submucosa with neovascularization. No complications of bleeding, perforation and infection occurred. All albino rabbits kept normal dietary habit. No significant changes in weight were observed. Conclusion: Endoscopic autogenous fat transplantation in lower esophagus is considered as a safe and feasible method by preliminary animal experiments, which can provide a new option in the treatment of gastroesophageal reflux disease (GERD) and is worth further study.